The Concept of Social Support in the Qur'an and Its Impact on the Mental Health of Pregnant Women - Nurhayati, Eneng (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to explore the concept of social support as stated in the Qur'an and analyze its influence on the mental health of pregnant women. Through a literature study approach and thematic analysis of relevant verses of the Qur'an. Research results. Knowledge and correct understanding of the process of pregnancy and childbirth are also emphasized to reduce ignorance and anxiety. Reflecting on the verses of the Qur'an about the power and mercy of Allah can provide peace of mind. The psychological experience of pregnant women is seen as a test and a gift from Allah. The Qur'an provides comprehensive spiritual guidance to deal with emotional, physical, and cognitive challenges during pregnancy. By strengthening faith, being patient, grateful, relying on God, seeking knowledge, and supporting each other, pregnant women can go through their pregnancy with peace of mind and belief in God's help. The integration of Qur'anic values in understanding and addressing the psychological aspects of pregnancy not only provides spiritual peace but can also contribute to optimal mental and physical health for the mother and fetus, psychological well-being and a reduced risk of mental disorders in pregnant women. The practical implications of these findings are expected to provide insight into the development of social support interventions based on Islamic values to improve the mental health of pregnant women.